Factors affecting the academic performance of fourth year Bachelor of Science in Accountancy students of Pamantasan ng Lungsod ng Maynila for the Academic Year 2015-2016 - Baes, Edmon Jay Mark R.; Dalusong, Kenneth Paul B.; Lim, Jessrael R.; Salinas, Edwin G.; and Valencia, Iluderick Jr. D. 4 0 16; 5
u
Thesis: (Bachelor of Science in Accountancy)- -- Pamantasan ng Lungsod ng Maynila, 2016.
Keywords: 2 -- 0; 6; 20; 20; 2